Vibronic coupling effects in resonant auger spectra of H2O - Eroms, Matthis; Jungen, Martin; Meyer, Hans-Dieter (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2012)
We present a theoretical investigation of the resonant Auger effect in gas-phase water. As in our earlier work, the simulation of nuclear dynamics is treated in a one-step picture, because excitation and decay events cannot be disentangled. Extending this framework, we now account for the vibronic coupling in the cationic final states arising from degeneracies in their potential energy surfaces (PESs). A diabatization of the cationic states permits a correct treatment of non Born-Oppenheimer dynamics leading to a significantly better agreement with experimental results. Moreover, we arrive at a more balanced understanding of the various spectral features that can be attributed to nuclear motion in the core-excited state or to vibronic coupling effects. The nuclear equations of motion have been solved using the multiconfiguration time-dependent Hartree (MCTDH) method. The cationic PESs were recalculated using the coupled electron pair approach (CEPA) whereas previously a multireference configuration interaction method had been employed.